Judge Frank Creede, Jr. Swears In Superior Court Judge Mario Olmos - Watkins, Howard::::::::: (1983)
Court reporter Kathy Papadakis holding transcript; Judge Victor Papadakis hugging Judge Mario Olmos Law Offices of Olmos and Frampton at 925 N St. #150, Fresno